Comparison of interior propagation models of the Wi-Fi network at the 5785 MHz band through RSSI measurements (MASKAY, 2025)
This study presents a comparative analysis of the Cost231-Multi-Wall Model, the Motley-Keenan Model, the Modified Free Space Model, and the Log-Normal Shadowing Path Loss Model, applied to a 5G Wi-Fi network in an indoor analysis. The research seeks to recommend the most appropriate small-scale propagation model based on empirical measurements of signal strength. Initially, the router is located within the analysis area. Then, a detailed sketch is made in SketchUp, locating 133 points around the primary router, covering the entire indoor area of the analysis, ensuring an accurate assessment of the cellular network coverage. Subsequently, with the data collected over three campaigns, propagation losses were calculated to determine the theoretical power of each model and compare the measured power values with the theoretical power values to obtain a specific model. The four propagation models analyzed in the evaluator are based on data obtained in the range [-20 to-91] dBm. It was concluded that the Keenan-Motley propagation model offered a better fit to the measurements, presenting a value of 12.59 dB. In contrast, the Cost 231 model showed a value of 17.18 dB, the Modified Free Space model showed a value of 26.47 dB, and the Log-Normal Shadowing Path Loss model showed a value of 27.57 dB, indicating a greater discrepancy concerning the measured data. This model demonstrated greater accuracy in predicting the reception power compared to the other analysis models, adapting better to the specific characteristics of the environment. These results highlight the importance of strategically locating the router; therefore, it is recommended to locate it in a central location.
Keywords: Propagation Models; indoor 5G Wi-Fi; signal strength measurement; model comparison; router placement